Theoretical and experimental research into manufacturing of silicate products without thermal treatment - Vinnichenko, Varvara; Krot, Alexander; Vitsenko, Natalia (Eastern-European Journal of Enterprise Technologies, 2016)
We conducted thermodynamic studies of creation of the compounds of calcium hydrosilicates. The comparison was performed of the use of calcium hydroxide and calcium oxide in the calciumsilicate mixture. It is demonstrated that the higher thermodynamic probability of reaction is characteristic for calcium oxide. The values of enthalpy of reaction with calcium oxide were examined. Reaction with calcium oxide has an exothermic character. The use of calcium hydroxide leads to the endothermic nature of reaction. The effect of mechanical activation and chemical activation on strength of the samples of silicate brick is confirmed. The joint action of these types of activation is more effective. The occurrence of a synergetic effect with the joint action on the mixture of mechanical and chemical activation is shown. It was established that the joint action of mechanical and chemical activation creates conditions for reactions of the creation of calcium hydrosilicates without an autoclave. This is important since this makes it possible to create more energyefficient technologies for silicate building articles.